Monitoring System of the ATLAS ITk Laboratory. Issue 1 (1st November 2022) - Sykora, Martin; Dolezal, Zdenek; Kodys, Peter; Kroll, Jiri
Abstract : The ATLAS ITk Upgrade project, culminating in the installation into the experiment in 2026, enters this year its production period. Cooperating laboratories dealing with the strip part of the project needs to meet various conditions in clean rooms and testing environments to ensure safety for production components during assembly and measurement procedures. One of the ITk laboratories, located in Prague, prepared for modules' production is presented as a model case. For this purpose, dedicated DAQ software called ITSDAQ is used together with the slow control monitoring system based on RS232/GPIB standards, MySQL database entry and Grafana visualization platform. Data are stored in the local database storage, a subset of them and the test results are also sent into the ITk Production Database. Such an integrated tool offers real-time plotting of crucial parameters and the possibility of receiving an immediate notification in case of exceeding any threshold.